The Impact of Using a Cloud-Based Learning Management System on Access and Quality of Education - Syamsu Rijal; Guijiao Zou; Lie Jie; Caitlin Demsky (Yayasan Adra Karima Hubbi, 2024)
Background:The use of a cloud-based learning management system is the use of cloud computing technology to manage and access the online education system. By using this technology, educational institutions can provide learning materials, manage courses, and interact with students digitally via the internet. Research purposes:This research was conducted with the aim of seeing how the use of a cloud-based learning management system can improve access and quality of education by creating an online learning management system that can be accessed anytime and anywhere, as well as making it easier to manage learning materials, course management and digital interaction with students. . Method:The method used in this research is quantitative methods.This method is a way of collecting data and numbers that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From the research results, it can be seen that the impact of using a cloud-based learning management system can improve access and quality of learning. Apart from that, the use of a Cloud-Based Learning Management System can also improve the competitive performance of teachers in schools. Conclusion:From this research, researchers can conclude that the impact of using a cloud-based learning management system helps people acquire the skills needed to meet the demands of an ever-changing job market. However, LMS use must be done carefully and incorporated well into an institution's educational strategy to create an inclusive, adaptive, and sustainable learning experience.